1996
DOI: 10.1074/jbc.271.25.14668
|View full text |Cite
|
Sign up to set email alerts
|

A Genetic Defect in Phosphatidylcholine Biosynthesis Triggers Apoptosis in Chinese Hamster Ovary Cells

Abstract: We have investigated the cell death of a Chinese hamster ovary mutant (MT-58) with a thermo-sensitive CTP:phosphocholine cytidylyltransferase, the rate-limiting enzyme of the CDP-choline pathway for phosphatidylcholine biosynthesis (Esko, J. D., Wermuth, M. M., and Raetz, C. R. H. (1981) J. Biol. Chem. 256, 7388-7393). After MT-58 cells were shifted to the restrictive temperature of 40 degrees C, the cytidylyltransferase was inactivated immediately leading to a decrease in phosphatidylcholine biosynthesis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
169
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(178 citation statements)
references
References 30 publications
8
169
0
1
Order By: Relevance
“…Therefore, PC is important for maintaining cellular integrity and cell growth. Furthermore, several studies have clearly demonstrated that PC deficiency alone may induce apoptosis [8]. Although we identified PC only in the pregnant group, as shown in Table 2, this result does not mean that it is absent in the non-pregnant group.…”
Section: Discussionmentioning
confidence: 46%
“…Therefore, PC is important for maintaining cellular integrity and cell growth. Furthermore, several studies have clearly demonstrated that PC deficiency alone may induce apoptosis [8]. Although we identified PC only in the pregnant group, as shown in Table 2, this result does not mean that it is absent in the non-pregnant group.…”
Section: Discussionmentioning
confidence: 46%
“…An alternative pathway to generate PC implies the methylation of PE by phosphatidylethanolamine-N-methyl-transferase (PEMT) (Vance et al, 1997). However, this pathway is not relevant in mammalian cells as demonstrated by restoration of PC synthesis by PEMT transfection experiments in cells rendered temperature-sensitive mutant for CT (MT58 cell line) (Esko et al, 1981(Esko et al, , 1982Houweling et al, 1995;Cui et al, 1996). The inability of PEMT to rescue MT58 cells under restrictive temperature from apoptosis suggests that the PC species generated from the Kennedy pathway and the PEMT pathway are functionally different (Cui and Houweling, 2002).…”
Section: Mechanism Of Action Of Choline Kinase Inhibitorsmentioning
confidence: 99%
“…Indeed, recent work shows that defective synthesis of PtdCho is by itself sufficient to cause apoptosis ; thus mutant Chinesehamster ovary (' CHO ') cells possessing a temperature-sensitive cytidylyltransferase undergo apoptosis when exposed to temperatures which inactivate this enzyme [28], and HeLa cells or HL60 cells are rescued from apoptosis caused by inhibitors of PtdCho synthesis if cytidylyltransferase is up-regulated [26] or if lysoPtdCho is added as an alternative source of PtdCho [27]. There is even a possibility that C # -ceramide as a natural metabolite could affect normal lipid synthesis, since at least in HL60 cells, endogenous C # -ceramide can be formed from platelet-activating factor [29].…”
Section: Table 1 Changes In Distribution Of Lipid Radioactivity In Hlmentioning
confidence: 99%